The association of Helicobacter pylori CagA EPIYA motifs and vacA genotypes with homologous recombination repair markers during the gastric precancerous cascade. Issue 2 (June 2020) - Mi, Yang; Dong, Haibin; Sun, Xiangdong; Ren, Feifei; Tang, Youcai; Zheng, Pengyuan
Background: Helicobacter pylori -induced DNA damage and impaired homologous recombination repair are vital molecular mechanisms for gastric cancer, which mainly count on its virulence factors cytotoxic-associated gene A (CagA) and vacuolating cytotoxin A (VacA). However, the relationship between H. pylori CagA EPIYA motifs and vacA genotypes with DNA damage and homologous recombination repair markers is still not clear. Methods: H. pylori positive and negative gastric biopsies were taken from 165 subjects with different gastric precancerous pathologic stages, and DNA damage marker γH2AX and key homologous recombination repair proteins (CtIP and Rad51) were investigated for their association with H. pylori CagA EPIYA motifs and vacAs-, m-, i-, and d-region genotypes and histology (Sydney classification). Results: Out of 165 patients, 78 were identified as H. pylori -positive. CagA EPIYA motifs were identified as AB, ABC, and ABD in 2 (3.3%), 21 (35%), and 37 (61.7%) patients, respectively, while vacA alleles were identified as: s1, s2, m1, m2, i1, i2, d1, and d2 in 50 (89.3%), 6 (10.7%), 24 (42.9%), 32 (57.1%), 45 (80.4%), 11 (19.6%), 40 (71.4%), and 16 (28.6%) patients, respectively. vacAs1m1i1d1, s1m2i1d1, and s1m2i2d2 were the most prevailing genotypes. γH2AX was highly localized in H. pylori -positive tissues with corresponding CagA EPIYA motifs and vacA genotypes, while Rad51 and CtIP signals were weak. Conclusion: H. pylori were positively correlated with the DNA damage marker in precancerous lesions, but were negatively correlated with the key homologous recombination repair proteins, which may be due to the specific CagA EPIYA motifs and vacA genotypes.